Zur Phylogenie der Parametabola, unter besonderer Berücksichtigung der Phthiraptera. - Königsmann, Eberhard (Contributions to Entomology = Beiträge zur Entomologie, 1960)
The relationship within the Parametabola is discussed. The interpretation of the hitherto known characters leads to the conclusion that the Mallophaga not at all, Amblycera and Ischnocera apparently, Parametabola, Zoraptera, Acercaria, Hemipteria, Psocodea, Phthiraptera and group A in all probability and Anoplura certainly are natural monophyletic groups. In full obscurity remains the question, wether the origin of the Phthiraptera was on Mammals or on birds. The presumable age of the groups, i. e. the point of their separation, is discussed.